The Effect of Corporate Culture and Compensation toward Employee Performance through Employee Motivation after the Merger (PT Bina Pertiwi Case Study) - Agus Mustofa; Nila Krisnawati; Firdaus Basbeth (Directorate of Academic Research and Community Services, 2022)
Changes that occur very quickly cause companies to be more innovative and adaptive to the changes themselves. Employee and company performance is important because it is related to its sustainability in the long term. On the other hand, companies must also pay attention to cultural, compensation, and motivational factors to achieve an effective and efficient performance. This research examines the influence of corporate culture and compensation on employee performance with motivation as an intervening variable. This is a quantitative study using primary data; Structural Equation Modeling (SEM) PLS is used to analyze the data obtained from PT Bina Pertiwi. The researcher obtained 100 respondent data based on predetermined criteria, which were analyzed using SmartPLS software. According to the findings of this study, work culture has a positive impact on employee performance. Employee motivation mediates corporate culture on employee performance, but employee motivation does not mediate compensation effect on employee performance. PT Bina Pertiwi needs to improve the factors that affect employee motivation and performance such as work culture